Unfolding various academic mobility experiences of Southeast Asian women. Issue 12 (2nd December 2017) - Nguyen Thi Phuong Tam, Therese; Araújo, Emília
Abstract: This article draws on data from a qualitative research study undertaken with the main aim of investigating the issue of the gender dimension of the academic mobility of Southeast Asian women. Our research describes Southeast Asian women's experiences of mobility, narrating why they choose to be mobile, how the experience of going abroad was responded to and/or rejected by their family, how they experienced life in a different country, and what evaluations they make about these experiences in personal, familial, and professional terms. The article stresses the need to improve the understanding of the factors that are still determining the chances of women to be mobile and obtain fruitful gains from these experiences. For this to be attained, the article follows through an intersectional approach to mobility, considering it is of much use as it allows to comprehend that the disadvantages associated with gender are cumulative, multi-layered, resulting from effects of several variables, including of the emotional, social, economic, and political contexts.